PROBLEMATIKA PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM (Studi terhadap Peraturan Pemerintah Nomor 17 Tahun 2010 dan Peraturan Menteri Pendidikan Nasional No. 19 Tahun 2007) - Nursalim Nursalim (Millah: Journal of Religious Studies, 2016)
As the country with the largest Muslim population, Indonesia has Islamic educational institutions, such as the shape of schools, and boarding. Only the Islamic educational institutions have not been managed optimally. This fact is evidenced by a variety of management issues in Islamic educational institutions both in terms of curriculum, educators, learners, educators, financial administration, classroom management, and infrastructure. The complexity of these problems need to be resolved. To that end, this article will discuss in detail the problems of management of Islamic educational institutions that happened and find the right solution to give a discourse to the managers of Islamic educational institutions related to the management of Islamic educational institutions is good and right.